EFEK HARGA, PROMOSI, DAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK INDIHOME DI KANTOR PLASA TELKOM PELITA BATAM - Ade Tryana Putri; Bambang Satriawan (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2017)
This research aims to test and prove the effect price, promotion, and product toward buying decision of Indihome in Plasa Telkom Pelita Batam. The population of this study were customer of Plasa Telkom Pelita Batam. In determining sample, the authors use Probability sampling with Randhom Sampling. The respondents in this study were 126 customer and taken by Slovin method with 10% standart error. This study uses quantitative data from their prime source collected through questionnaires. The data analysis technique applied test the hypothesis is quantitative analysis, the validity, reliability test, classic assumption test, multicoloniarity test, heteroscedasticity test, normality test, multiple linear regression analysis, t-test, f-test, and the coefficient of determination R2. The results analysis showed that Variable price, partially has positive and significant effect on buying decision. Variable promotion partially has positive and significant effect on buying decission. And product partialy also has positive and significant effect on buying decission of customer at Plasa Telkom Pelita. Variable of price, promotion, and product simultaneously has significant effect on buying decision at Plasa Telkom Pelita Batam.